Vesicle structures from bolaamphiphilic biosurfactants: experimental and molecular dynamics simulation studies on the effect of unsaturation on sophorolipid self-assemblies - Dhasaiyan, Prabhu; Pandey, Prithvi Raj; Visaveliya, Nikunjkumar; Roy, Sudip; Bhagavatula L. V. Prasad (Chemistry-A European Journal, 2014)
The formation of giant-vesicle-like structures by self-assembling linolenic acid sophorolipid (LNSL) molecules is revealed. Sophorolipids belong to the class of bolaamphiphilic glycolipid biosurfactants. Interestingly, the number of double bonds present in the hydrophobic core of sophorolipids is seen to have a great influence on the type of self-assembled structures formed. Dye encapsulation results establish the presence of an aqueous compartment inside the LNSL vesicles. Molecular dynamics simulation (MD) studies suggest the existence of two possible conformations of LNSLs inside the self-assembled structures and that LNSL molecules arrange in layered structures.
Keywords: bolaamphiphiles; MD simulations; Self-assembly; sophorolipids; vesicles

Phase diagram of self-assembled sophorolipid morphologies from mesoscale simulations - Sarkar, Sujit; Chakraborty, Souvik; Roy, Sudip (Journal of Molecular Liquids, 2018)
We have constructed a phase diagram from the self-assembled morphologies of linolenic acid sophorolipid in water by performing mesoscale simulations in different concentrations. The dependence of morphologies and its properties of the self-assembled structure as a function of the concentration of bolaamphiphile in water are investigated. Two hydrophilic head groups and one hydrophobic tail group of bolaamphiphile have been mapped to beads for mesoscale simulation. The interaction parameters between different beads are calculated using Flory-Huggins solution theory. Flory-Huggins x-parameters have been calculated from atomistic simulation and experimental data of pure components constituting linolenic acid sophorolipid. We have obtained different self-assembled morphologies depending upon the concentrations of sophorolipid in water. We have explored the arrangements of hydrophobic and hydrophilic groups of the sophorolipid chains in the different morphologies. The sophorolipid chains found to be present in different structural arrangements. The residence time and flip frequency of these lipids in different orientations have been calculated and discussed in this work. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Bolaamphiphile; Flip frequency; Mesoscale simulation; Orientation of chains; Self-assembly